In Their Own Words: Re-Examining Gender Differences in Career Interests and Motivations in a New Generation. - Barth, Joan M.; Masters, Stephanie (Sex Roles, 2024)
Social role theory (Eagly, 1987) posits that gender differences in career interests are consistent with normative social role expectations, with men assuming more agentic roles and women assuming more communal roles. To account for historical shifts in occupations and social roles, this mixed-methods study re-examines gender differences in career interests and motivations with a sample of 501 eighth graders (52% girls; 40% White) from the U.S. Findings indicated that boys and girls had distinct career interests and motivations. Despite preferring careers that were generally dominated by their own gender, students perceived their chosen career as being more gender balanced than U.S. labor force statistics indicate. This misperception might be the result of a preference for less stereotypical occupations, and may reflect a unique characteristic of the next-generation workforce. In addition, boys were more likely than girls to indicate that salary factored into their career choice; whereas girls were more likely than boys to indicate that a desire for helping others or working with children motivated their career choice, consistent with social role theory. Some motivational factors that are typically linked with young adult career preferences were not strong factors in younger adolescents' career interests, perhaps due to the developmental status of participants or a generational shift in values. A generational shift in values may account for the presence of a relatively understudied motivational factor, occupation creativity, which was important for both boys and girls. Addressing gender differences in the motivations and goals that affect career interests may both alleviate workforce shortages and achieve a less gender segregated work environment.